Recensão: CORNU, Marie [et al.], dir. - 1979: Genèse d’une loi sur les archives. Paris: Ministère de la Culture, 2019. (Travaux et documents; n. 41). ISBN 978-2-11-157027-6 - Rodrigues, Georgete Medleg (Páginas a&b: arquivos e bibliotecas, 2021)
The book is one of the results of the research program entitled Mémoloi, the memory of the great laws of protection the heritage culturel which, as highlighted in the text, has already produced two other studies anchored in the investigation of major laws for the protection of heritage; the creation of a digital platform on the historical monuments belonging to the Architecture and heritage media library exhibition (2018-2019) entitled Juger le patrimoine. Institutions such as the Institut des sciences sociales et du politique/CNRS contributed to its realization.